Ca2+ Signaling and Cell Death Induced by Protriptyline in HepG2 Human Hepatoma Cells. Issue 11 (2nd June 2016) - Wang, Jue‐Long; Chou, Chiang‐Ting; Liu, Kang; Liang, Wei‐Zhe; Cheng, Jin‐Shiung; Chang, Hong‐Tai; Chen, I‐Shu; Lu, Ti; Kuo, Chun‐Chi; Yu, Chia‐Cheng; Shieh, Pochuen; Kuo, Daih‐Huang; et al.
ABSTRACT: The effect of protriptyline on Ca 2+ physiology in human hepatoma is unclear. This study explored the effect of protriptyline on [Ca 2+ ]i and cytotoxicity in HepG2 human hepatoma cells. Protriptyline (50–150 μM) evoked [Ca 2+ ]i rises. The Ca 2+ entry was inhibited by removal of Ca 2+ . Protriptyline‐induced Ca 2+ entry was confirmed by Mn 2+ ‐induced quench of fura‐2 fluorescence. Except nifedipine, econazole, SKF96365, GF109203X, and phorbol 12‐myristate 13 acetate did not inhibit Ca 2+ entry. Treatment with the endoplasmic reticulum Ca 2+ pump inhibitor 2, 5‐di‐tert‐butylhydroquinone (BHQ) inhibited 40% of protriptyline‐induced response. Treatment with protriptyline abolished BHQ‐induced response. Inhibition of phospholipase C (PLC) suppressed protriptyline‐evoked response by 70%. At 20–40 μM, protriptyline killed cells which was not reversed by the Ca 2+ chelator 1, 2‐bis(2‐aminophenoxy)ethane‐N, N, N′, N′‐tetraacetic acid‐acetoxymethyl ester (BAPTA/AM). Together, in HepG2 cells, protriptyline induced [Ca 2+ ]i rises that involved Ca 2+ entry through nifedipine‐sensitive Ca 2+ channels and PLC‐dependent Ca 2+ release from endoplasmic reticulum. Protriptyline induced Ca 2+ ‐independent cell death.